Integration of silver nanostructures in wireless sensor networks for enhanced biochemical sensing - M. Sahaya Sheela; S. Kumarganesh; Binay Kumar Pandey; Mesfin Esayas Lelisho (Discover Nano)
Abstract Integrating noble metal nanostructures, specifically silver nanoparticles, into sensor designs has proven to enhance sensor performance across key metrics, including response time, stability, and sensitivity. However, a critical gap remains in understanding the unique contributions of various synthesis parameters on these enhancements. This study addresses this gap by examining how factors such as temperature, growth time, and choice of capping agents influence nanostructure shape and size, optimizing sensor performance for diverse conditions. Using silver nitrate and sodium borohydride, silver seed particles were created, followed by controlled growth in a solution containing additional silver ions. The size and morphology of the resulting nanostructures were regulated to achieve optimal properties for biochemical sensing in wireless sensor networks. Results demonstrated that embedding these nanostructures in Polyvinyl Alcohol (PVA) matrices led to superior stability, maintaining 93% effectiveness over 30 days compared to 70% in Polyethylene Glycol (PEG). Performance metrics revealed significant improvements: reduced response times (1.2 ms vs. 1.5 ms at zero analyte concentration) and faster responses at higher analyte levels (0.2 ms). These outcomes confirm that higher synthesis temperatures and precise shape control contribute to larger, more stable nanostructures.The enhanced stability and responsiveness underscore the potential of noble metal nanostructures for scalable and durable sensor applications, offering a significant advancement over current methods.